2020
DOI: 10.1016/j.jvs.2019.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Open Repair of Juxtarenal Abdominal Aortic Aneurysms: A Multicentre Retrospective Study in Five French Academic Centres

Abstract: Objectives: With a focus on renal function, the goal of this multicentre study was to assess peri-operative complications and late mortality of open surgical repair (OSR) of juxtarenal abdominal aortic aneurysms (JRAAA). Methods: From February 2005 to December 2015, 315 consecutive patients undergoing elective OSR of a JRAAA in five French academic centres were evaluated retrospectively. The definition of JRAAA was an aortic aneurysm extending up to but not involving the renal arteries, i.e., a short neck <10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Chaufour et al 30 reported on OSR of 315 JRAAAs across 5 centers in France over a 10-year period from 2005, 67.3% via a RP approach. They found an early mortality of only 0.9% with their series representing a less advanced burden of disease, having a lower median maximal diameter (59.7 mm) and a very low proportion of supraceliac clamping (3.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Chaufour et al 30 reported on OSR of 315 JRAAAs across 5 centers in France over a 10-year period from 2005, 67.3% via a RP approach. They found an early mortality of only 0.9% with their series representing a less advanced burden of disease, having a lower median maximal diameter (59.7 mm) and a very low proportion of supraceliac clamping (3.5%).…”
Section: Discussionmentioning
confidence: 99%